MATERNAL AND FETAL OUTCOME IN RENAL TRANSPLANT RECIPIENTS - Syed, Wajeeha; Sheikh, Louman (Journal of Postgraduate Medical Institute, 2017)
Objective: To determine maternal and fetal outcome in renal transplant recipients. Methodology: Retrospective analysis of the antenatal patients with renal transplant was done between January 1st 2005 till December 31st 2015 and maternal and fetal outcomes were determined. Data was entered and analyzed in SPSS version 20. Results: 08 pregnancies in 07 women who had undergone renal transplant were included in this study. The mean age at the time of transplantation was 25.29 ±5.5 years (16-32 years). 25% cases had gestational diabetes mellitus, 75% had anemia and 50% had urinary tract infection. The mean birth weight of babies was 2210 ±.638 grams (range1500-3400g). Preterm deliveries comprised 37.5% before 34 weeks and 50% after 34 weeks. 37.5% of the neonates needed neonatal intensive care unit admission. Conclusion: Pregnancy after renal transplant is safe for mother, fetus and the graft.